Contracting with Word-of-Mouth Management - Kamada, Yuichiro; Öry, Aniko (Management Science, 2020)
We propose a model for word-of-mouth (WoM) management where a firm has two tools at hand: offering referral rewards and offering a free contract. Current customers’ incentives to engage in WoM can affect the contracting problem of a firm in the presence of positive externalities of users. Formally, we consider a classic Maskin–Riley contracting problem for the receiver of WoM where the firm can pay the senders referral rewards and a sender experiences positive externalities if the receiver adopts. A free contract can incentivize WoM because the higher adoption probability increases the expected externalities that the sender receives. We characterize the optimal incentive scheme and show when the two tools serve as substitutes and complements to each other depending on whether the market is niche and whether the product is social. We show that offering a free contract is optimal only if the fraction of premium users in the population is small, which is consistent with the observation that companies that successfully offer “freemium” contracts oftentimes have a high percentage of free users. This paper was accepted by Juanjuan Zhang, marketing.